Analysis of students' initial scientific literacy of science in elementary school teacher education student - Astri Widyasari; Haryanto Haryanto (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
This study aimed to determine the level of scientific literacy possessed by prospective elementary school teachers at Yogyakarta State University. The method used in this research is a qualitative description. The research design used is descriptive quantitative research. The number of subjects in this study was 44 students of PGSD UNY. Data was collected through an online questionnaire survey. Questionnaire data were obtained through question items distributed to respondents in Google Form. The data collection was analyzed using Microsoft Excel and explained as a descriptive explanation. The results of this study indicate that the average scientific literacy ability in scientific competence as a whole is 66.08%, with the achievement category being